Parametric study on the compactibility of Ti-6Al-4V during direct powder rolling - Naicker, Hiranya (Department of Mechanical Engineering, 2020)
The widespread use of titanium and its alloys in structural applications has been limited to few highend applications. The dominant reason for this being cost implications. These high costs arise from extracting titanium from its mineral form as well as that of the manufacturing processes to develop a final product. Since producing titanium products includes expensive starting stock, high machinability costs and high wastage, a need for a process that may minimize one or more of these factors is necessary. One such technology that exists is a branch of powder metallurgy (PM), direct powder rolling (DPR) which allows for a continuous approach to produce strip or sheet metal. Products developed by this process are however known to possess inferior properties to its wrought counterpart. The present study comprises of a parametric study observing how two different blends of powder differ in the development of Ti-6Al-4V strip by employing the blended elemental (BE) approach to direct powder rolling. The objectives of this work include predicting the compaction behavior of the two respective blends during powder rolling to inform the production of high density green strip and to compare the outcomes of the prediction method to experimentally determined results using a gravity-fed laboratory-scale rolling mill with roll diameter of 265 mm and roll width of 150 mm. Johanson’s rolling theory was applied to predict rolling outcomes and a fixed set of rolling parameters were implemented for the simulation and experimental segment of this dissertation. The two blends being investigated include blending titanium powder with an elemental blend consisting of aluminium and vanadium powders (B1) and a master alloy blend of a 60Al-40V master alloy (B2). These two blends were used to validate the Johanson simulated rolling data. Fixed parameters applied to the rolling mill included using a roll speed of 14 rpm, roll face width of 65 mm and gravity-fed hopper outlet diameter of 25 mm. Variable roll gaps of 0.5, 1 and 1.5 mm were studied. Average relative green densities of B1 and B2 strips achieved at a roll gap of 1 mm were 77% and 73% respectively. Rolling performance of the B1 powder blend were higher than that of B2, reaching higher green densities and showing superior formability, as rolling at smaller roll gaps was achievable for B1 and not B2. Green strength of B1 and B2 strips at a roll gap of 1 mm reflected similar outcomes where B1 strips required a greater breaking load to fracture samples when compared to B2 indicating a stronger self-supporting compact. Furthermore, the Johanson rolling model proved to overestimate reasonable roll pressure values, although, the general trend of compactibility between B1 and B2 powder blends was reasonably predicted showing B1 to be more compressible than B2 during powder rolling. iv Subsequent sintering at 1200 °C for 3 hours in a vacuum environment was applied to green strips to further densify and homogenize strips. Average relative sintered densities achieved for B1 and B2 strips rolled at a roll gap of 1 mm were 78% and 87% respectively. While green densities of B1 strips were higher than that of B2 strips, it was evident that the addition of the 60Al-40V master alloy to blend B2 resulted in superior sinterability as final sintered densities surpassed that of B1, even when starting at a lower green density after rolling. SEM/EDX was used to evaluate what effect sintering had on homogenization. A standard wrought Ti-6Al-4V specimen was used as the benchmark to compare homogenization results. B2 strips homogenized more than B1 strips when comparing to the baseline wrought sample. It was concluded that both B1 and B2 powders used to create Ti-6Al-4V strip by direct powder rolling (DPR) exhibited high levels of porosity and a subsequent step is necessary to fully densify the material. While B1 strips exhibit superior rollability with higher green densities and green strength; after applying a sintering practice to both B1 and B2 strips, B2 sintered densities surpassed those of B1 and prove to homogenize to a greater degree than B1 strips. The superior roll compaction ability and inferior sinterability for B1 powders was attributed to the elemental powder, aluminium. While the addition of ductile aluminium to B1 aids roll compaction, its low melting point results in large pores evolving at sintering temperatures almost twice its melting point.